Environmental Health Perceptions in University Classrooms: Results From an Online Survey During the COVID-19 Pandemic in the United States and Colombia - Coronado, Maria Camila; Rockcastle, Siobhan; Kwok, Alison (Frontiers in Built Environment, 2021)
At the start of the COVID-19 pandemic, multiple institutions mobilized to create recommendations that maximize indoor environmental quality to keep building occupants as safe as possible. Many of those recommendations were implemented in buildings across the world even before the presence of field data validated their effectiveness. However, as the pandemic raised awareness of the risks present in the air quality of everyday built environments, little is known about how occupants perceive these interventions or how they will perceive buildings when activities resume with an in-person requirement. This paper presents results from an online survey, conducted from April 23rd to May 8th, 2021, and offers a window into the perceptions of university students on a variety of physical intervention strategies that have been promoted for the return to classrooms. Our analysis explores differences in these perceptions between students from Colombia and the United States, where the vaccination rates of the population as of May 2021 differed substantially. An anonymous online survey was disseminated to students of higher academic institutions using images portraying 3D models of classrooms and written prompts to assess perceptions. Health risk and health promotion perceptions were evaluated using four categories: visual connection to the outdoors, occupant density, additional furnishings, ventilation system type, and number of operable windows. While the effectiveness of these strategies from an epidemiological standpoint was not considered, this survey aimed to measure the perceived effectiveness of these strategies as students prepare to return to in-person education in the classroom. Our analysis found a significant effect of different degrees of ‘connection to the outdoors’ and ‘occupant density’ on both perceived health risk and health promotion in both countries. Respondents ranked strategies like mask-wearing and natural ventilation as important interventions when considering a return to the classroom. Perceptions of health risk and health promotion between students taking classes in the US and Colombia were significantly different regarding the presence of additional furnishings, and ventilation systems and number of windows in a classroom. The results presented here may shed light on how aspects of the built environment help shape perceptions of healthy environments during the pandemic.